Analysis of Factors That Encourage Entrepreneurial Interest of Students of the Faculty of Economics, Universitas Nahdlatul Ulama, North Sumatra on Digital Transformation - Ahmad Syukur Nasution; Fatimah Pohan; Ramadani Ramadani (Journal of Management, Economic, and Accounting, 2026)
Digital transformation has changed the economic landscape and opened up huge opportunities for student entrepreneurship. This study aims to analyze the influence of entrepreneurial knowledge, achievement motivation, self-efficacy, family environment, and digital literacy on the entrepreneurial interest of students of the Faculty of Economics, Nahdlatul Ulama University of North Sumatra (UNUSU) in the digital era. This research is a quantitative research with active student subjects of the Faculty of Economics UNUSU. Primary data was collected through the distribution of questionnaires and analyzed to see the influence of these variables both partially and simultaneously on entrepreneurial interest. The results of this research are expected to make a theoretical contribution to the development of entrepreneurial management science as well as practical benefits for universities in designing entrepreneurship coaching programs that are adaptive to digital technology. The limitations of this study are focused on measuring entrepreneurial interest and do not analyze real business performance.